On impersonal feeling. Mario Perniola’s studies on the aesthetics era - Hanza, Kathia (2017)
The article analizes Perniola’s understanding of aesthetics. According to Perniola, the study of aesthetics (aísthesis) as a sphere of feeling provides interpretative clues for understanding of the contemporary world, characterized by theimpoverishment of individual experience and the incapacity for proper feeling. The conformity of feeling, which has become impersonal nowadays, is explained on the one hand through archaeology, which makes visible the stratifications of the “already felt”, and on the other hand, through genealogy, which discovers the active dimension of feeling.